Medication Therapy Review of Elderly Who’s Receiving Insulin - Athiyah, Umi; Aditama, Lisa (Journal of Pharmacy Practice and Community Medicine)
Background : Patients with chronic disease with stable conditions require continuity of treatment accessible through referral services at primary health facilities.1 There was potential for patients to receive different kind of services by health care practitioners. It may also caused drug-related problems.2 Pharmacist had strategic role in the medication management of chronic diseases, to deliver pharmaceutical care.3 Aim: To identify drug related problems of elderly patient who’s receiving insulin. Materials and Methods : A logbook of chronic disease treatment in the integrated service station for elderly (Posyandu Lansia) at Indonesia, East Java, Surabaya was assessed with the Medication Therapy Review (MTR) as systematic process of collecting patient information specifically, to identify drug-related issues, developing a priority list of drug-related issues, and making plans to address them. Results : There was many drug therapy problems such as inappropriateness of insulin types selection, drug substitution without information, patient received an excess amount of insulin pen, incorrect insulin storage and needs attention due to insulin stability. Discussion: Evolving role of community pharmacist through MTR service can improve the patient's understanding of the medications, address any concerns of drug therapy problems, empowering patients to perform self-management and patient health conditions especially in elderly patient and patient using specific device.
Keywords: continuity of care; drug-related problems; community pharmacist; MTR